Sapientia iudicis: Brevi note in calce a un passo di Cicerone - Bellodi Ansaloni, Anna (Tesserae iuris, 2023)
Cicero, in an excerpt of the oratio pro Cluentio (58.159), exhorts iudices to sapientia, virtue in which timeless values such as religio, aequitas and fides are brought together. This virtue is fundamental in order either to interpret the ratio of law or to judge according to law and to conscience.